IstirÄtÄ«jiyyah MahÄrah al-IstimÄÊ¿ fÄ« TaÊ¿lÄ«m al-Lughah al-Ê¿Arabiyyah li al-NÄá¹iqÄ«n bi GhairihÄ, al-KitÄb al-AsÄsiy bi MaÊ¿had al-Khurá¹Å«m al-Dauliy NamÅ«Å¼ajan - Hasan, Nahla (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
The article dealt with the strategies of listening skills and their acquisition for non-native Arabic language learners through the introductory book at the Khartoum International Institute for the Arabic language at the intermediate level. The study intends to know the strategies used in implementing the listening skill as one of the primary and practical skills in teaching language and communication with others, and the listening skill has elements that are not based only on receiving audible sounds and understanding the meanings of words and sentences. Instead, it requires using the senses of sight and hearing together besides the mind. To achieve this, the researcher followed the following methodological and procedural steps: The study tool is: the interview and attendance of three lectures for listening lessons at the Khartoum International Institute, and directing interview questions to the two teachers in the second semester of the year 20/2021 AD. The number of learners was between twenty-five to thirty learners from countries: Indonesia, Nigeria, China, Comoros, and others. The study relied on the descriptive approach based on observation, induction, and analysis. It is carried out according to several strategies, including direct and indirect.ØªÙ†Ø§ÙˆÙ„Øª Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ ÙˆØ¥ÙƒØ³Ø§Ø¨Ù‡Ø§ Ù„Ù…ØªØ¹Ù„Ù…ÙŠ Ø§Ù„Ù„Ù‘ÙØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØŒ Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø®Ø±Ø·ÙˆÙ… Ø§Ù„Ø¯ÙˆÙ„ÙŠ Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ù…ØªÙˆØ³Ø·ØŒ Ø¨Ù‡Ø¯Ù Ù…Ø¹Ø±ÙØ© Ø§Ù„Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ ØªÙ†ÙÙŠØ°Â  Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ Ø¨ÙƒÙˆÙ†Ù‡Ø§ Ù…Ù† Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© ÙˆØ§Ù„ÙØ§Ø¹Ù„Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„Ù‘ÙØºØ© ÙˆØ§Ù„Ø§ØªØµØ§Ù„ Ù…Ø¹ Ø§Ù„Ø§ÙŽØ®Ø±ÙŠÙ†ØŒ ÙˆÙ„Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ Ø¹Ù†Ø§ØµØ±Â  Ù„Ø§ ØªØ³ØªÙ†Ø¯ ÙÙ‚Ø· Ø¥Ù„Ù‰ Ø§Ø³ØªÙ‚Ø¨Ø§Ù„ Ø§Ù„ØµÙˆØª Ø§Ù„Ù…Ø³Ù…ÙˆØ¹ ÙˆØ¥Ø¯Ø±Ø§Ùƒ Ù…Ø¹Ø§Ù†ÙŠ Ø§Ù„ÙƒÙ„Ù…Ø§Øª ÙˆØ§Ù„Ø¬Ù…Ù„Ø› Ø¨Ù„ ØªØªØ·Ù„Ø¨ Ø§Ø³ØªØ®Ø¯Ø§Ù… ØØ§Ø³ØªÙŠ Ø§Ù„Ø¨ØµØ± ÙˆØ§Ù„Ø³Ù…Ø¹ Ù…Ø¹Ù‹Ø§ Ø¨Ø¬Ø§Ù†Ø¨ Ø§Ù„Ø¹Ù‚Ù„ØŒ Ù…Ù† Ø£Ø¬Ù„ ØªØÙ‚ÙŠÙ‚ Ø°Ù„Ùƒ Ø§ØªØ¨Ø¹Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø§Ù„Ø®Ø·ÙˆØ§Øª Ø§Ù„Ù…Ù†Ù‡Ø¬ÙŠØ© ÙˆØ§Ù„Ø¥Ø¬Ø±Ø§Ø¦ÙŠØ© Ø§Ù„Ø¢ØªÙŠØ©: Ø£Ø¯Ø§Ø© Ø§Ù„Ø¯Ù‘ÙØ±Ø§Ø³Ø© Ù‡ÙŠ: Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø©Â  ÙˆØØ¶ÙˆØ± Ø«Ù„Ø§Ø« Ù…ØØ§Ø¶Ø±Ø§ØªÂ  Ù„Ù„Ø¯Ø±ÙˆØ³ Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹Â  Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø®Ø±Ø·ÙˆÙ… Ø§Ù„Ø¯ÙˆÙ„ÙŠØŒ ÙˆØªÙˆØ¬ÙŠÙ‡ Ø£Ø³Ø¦Ù„Ø© Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© Ù„Ù„Ù…Ø¹Ù„Ù…ØªÙŠÙ† ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠ Ø§Ù„Ø«Ø§Ù†ÙŠ Ù„Ù„Ø¹Ø§Ù… 20/2021Ù…ØŒ Ø£Ù…Ù‘Ø§ Ø¨Ø§Ù„Ù†Ù‘Ø³Ø¨Ø© Ù„Ù„Ù…ØªØ¹Ù„Ù…ÙŠÙ†ØŒ ÙÙ‚Ø¯ Ø§Ù†ØØµØ± Ø¹Ø¯Ø¯Ù‡Ù… Ù…Ø§ Ø¨ÙŠÙ† Ø®Ù…Ø³ ÙˆØ¹Ø´Ø±ÙŠÙ† Ø¥Ù„Ù‰ Ø«Ù„Ø§Ø«ÙŠÙ† Ù…ØªØ¹Ù„Ù…Ø§ØŒ Ù…Ù† Ø¯ÙˆÙ„: Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§ØŒ ÙˆÙ†ÙŠØ¬ÙŠØ±ÙŠØ§ØŒ ÙˆØ§Ù„ØµÙŠÙ† ÙˆØ¬Ø²Ø± Ø§Ù„Ù‚Ù…Ø±ØŒ ÙˆØºÙŠØ±Ù‡Ø§ØŒ Ø§Ø¹ØªÙ…Ø¯Øª Ø§Ù„Ø¯Ù‘ÙØ±Ø§Ø³Ø© Ø¹Ù„Ù‰ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰Â  Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ø§Ø³ØªÙ‚Ø±Ø§Ø¡ ÙˆØ§Ù„ØªØÙ„ÙŠÙ„ØŒ ÙˆØªÙˆØµÙ„Øª Ø§Ù„Ø¯Ù‘ÙØ±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ù†ØªØ§Ø¦Ø¬ Ù…Ù† Ø£Ù‡Ù…Ù‡Ø§: Â Ø£Ù†Ù‘ ØªØ¯Ø±Ø³ "Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹" ÙŠØªÙ… ÙˆÙÙ‚ Ø¹Ø¯Ù‘Ø© Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ù…Ù†Ù‡Ø§ Ø§Ù„Ù…Ø¨Ø§Ø´Ø±Ø©ØŒ ÙˆØºÙŠØ± Ø§Ù„Ù…Ø¨Ø§Ø´Ø±Ø©.